2021
DOI: 10.1111/myc.13338
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19‐associated mucormycosis: An updated systematic review of literature

Abstract: In its wake, the COVID-19 pandemic has ushered in a surge in the number of cases of mucormycosis. Most cases are temporally linked to COVID-19; hence, the entity is described as COVID-19-associated mucormycosis (CAM). The present systematic review was undertaken to provide an up-to-date summary of the hitherto available literature on CAM. PubMed, Scopus and Google Scholar databases were systematically searched using appropriate keywords till 14 May 2021, to identify case reports/case series pertaining to mucor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
237
3
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(279 citation statements)
references
References 73 publications
(180 reference statements)
20
237
3
19
Order By: Relevance
“…The most common form of Mucormycosis reported in 42% of the patients was that of the rhino-orbital type. Corticosteroid therapy (85%) was mainly used for treatment [ 17 ]. In a retrospective multicenter study conducted in India between September and December 2020, it was discovered that 187 (65.2%) of 287 patients with mucormycosis had CAM, with a prevalence of 0.27 percent among hospitalized COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The most common form of Mucormycosis reported in 42% of the patients was that of the rhino-orbital type. Corticosteroid therapy (85%) was mainly used for treatment [ 17 ]. In a retrospective multicenter study conducted in India between September and December 2020, it was discovered that 187 (65.2%) of 287 patients with mucormycosis had CAM, with a prevalence of 0.27 percent among hospitalized COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…Out of these, 25 developed mucormycosis following recovery from COVID-19 and all except 1 received systemic steroids for management of COVID-1 while 3 received tocilizumab. Pal et al [11], in their systemic review, reported overall prevalence of diabetes to be 85% (Diabetes mellitus, type-2 in 79% including newonset in 16%, Diabetes mellitus type-1 in 6% cases). Nearly 29% in their study had presence of ketoacidosis.…”
Section: Discussionmentioning
confidence: 99%
“…This shows how the patients can be affected post-COVID. Pal et al [11] reported 39% of cases with concurrent CAM while the remaining 61% had a mean interval of 22 days between the two illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…An abrupt increase in the number of opportunistic fungal infections and outbreaks has been observed; in particular, several cases of COVID-19 associated pulmonary aspergillosis (CAPA) and COVID-19 associated mucormycosis (CAM) have been described. Multiple factors are associated with or lead to the development of those entities, including glucocorticoids and uncontrolled glucose, viral-induced lymphopenia, and direct damage to the airway epithelium, enabling Aspergillus , as well as Mucorales , to invade tissue and promote pulmonary aspergillosis or pulmonary mucormycosis (PM) [ 27 , 28 ].…”
Section: Populations At Risk and Clinical Manifestations Of Pulmonary Aspergillosis And Pulmonary Mucormycosismentioning
confidence: 99%